Common Sharks of Florida - Florida Sea Grant (EDIS)
Florida’s shark population is diverse and includes species that range in size from only a few feet to more than 40 feet in total length. Experts caution sea-goers to beware of sharks 6 feet or longer due to the damage they can cause in a single bite. Among the species that grow to this size and have been known to attack humans are bull sharks, tiger sharks, and great white sharks. Whites are seasonal visitors to Florida waters, and bulls and tigers are year-round residents, along with these other common species. This revised 4-page fact sheet was written by Florida Sea Grant, and published by the UF Department of Sea Grant, September 2013.